Escalating dose-multiple binge methamphetamine treatment elicits neurotoxicity, altering gut microbiota and fecal metabolites in mice. (February 2021) - Chen, Li-Jian; Zhi, Xu; Zhang, Kai-Kai; Wang, Li-Bin; Li, Jia-Hao; Liu, Jia-Li; Xu, Ling-Ling; Yoshida, Jamie Still; Xie, Xiao-Li; Wang, Qi
Abstract: Methamphetamine (METH) is an addictive and illegal psychostimulant drug that can cause multiple organ dysfunction, especially in the central nervous system (CNS). Gut microbiota have been implicated in development of various CNS-related diseases, via the gut-brain axis (GBA). However, effect of METH in the alteration of gut microbiota and fecal metabolites is unclear, whereas the relationship with METH-induced neurotoxicity remains unknown. In the current study, we investigated effect of METH on neurotoxicity in striatum and colonic damage by exposing BALB/c mice to an escalating dose-multiple binge regimen, and then analyzed protein expression using Western blot analysis. We further detected and sequenced the 16 S rRNA gene in fecal samples, and performed ultra-high-performance liquid chromatography-mass spectrometry (UHPLC-MS)-based metabolomics to analyze gut microbes and fecal metabolites. Exposure to METH significantly downregulated tyrosine hydroxylase (TH) proteins, but upregulated MAOA, Beclin1, Atg5, and LC3-Ⅱ. METH up-regulated inflammation-related factors, such as caspase1, TNF-α and IL-18, by activating the toll-like receptors 4 (TLR4)/myeloid differentiation factor 88 (Myd88)/nuclear factor κB (NF-κB) pathway and reduced occludin protein expression. In addition, METH exposure changed α and β diversities of gut microbiota. Specifically, METH exposure elevated relative abundances of pathogenic bacteria, but reduced those of probiotics. Metabolomics, combined with enrichment analyses revealed that METH exposure altered fecal metabolites. Our findings suggest that METH exposure induced autophagy in the CNS, elevated intestinal autophagy flora, leading to accumulation of fecal metabolites in the autophagy pathway, and causing enteritis. Moreover, METH promoted intestinal inflammation by increasing the relative abundance of the pathogenic bacteria in the intestinal tract, and reduced intestinal TJ protein expression. Highlights: Methamphetamine (METH) induces neurotoxicity and colonic inflammatory in mice. METH-exposed altered gut microbiota and fecal metabolites. METH-induced neurotoxicity, gut microbiota and fecal metabolites were closely related to autophagy.